2002
DOI: 10.1038/ni794
|View full text |Cite
|
Sign up to set email alerts
|

T-bet is a STAT1-induced regulator of IL-12R expression in naïve CD4+ T cells

Abstract: T helper type 1 (T(H)1) cell development involves interferon-gamma (IFN-gamma) signaling through signal transducer and activator of transcription 1 (STAT1) and interleukin-12 (IL-12) signaling through STAT4 activation. We examined here T-bet regulation and evaluated the actions of T-bet in STAT1- and STAT4-dependent T(H)1 development processes. We found that T-bet expression during T cell activation was strongly dependent on IFN-gamma signaling and STAT1 activation, but was independent of STAT4. Ectopic T-bet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
841
5
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 873 publications
(900 citation statements)
references
References 44 publications
40
841
5
14
Order By: Relevance
“…However, a subsequent report revealed that a cell-extrinsic regulatory circuit involving IFN-gR signaling via STAT1 largely maintained the high-level expression of T-bet in developing Th1 cells, rather than a cell-intrinsic pathway of T-bet autoactivation. 9 Because CD4 þ T cells from STAT1-deficient mice still expressed a low level of T-bet and could differentiate into Th1 cells, 23,24 it is possible that the OC2-mediated transactivation could be involved in the expression of T-bet in a different pathway from STAT1. Alternatively, OC2 could contribute to T-bet expression at some later time during Th1 development, when the stable expression of T-bet is already driven by the IFN-gR/STAT1 pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a subsequent report revealed that a cell-extrinsic regulatory circuit involving IFN-gR signaling via STAT1 largely maintained the high-level expression of T-bet in developing Th1 cells, rather than a cell-intrinsic pathway of T-bet autoactivation. 9 Because CD4 þ T cells from STAT1-deficient mice still expressed a low level of T-bet and could differentiate into Th1 cells, 23,24 it is possible that the OC2-mediated transactivation could be involved in the expression of T-bet in a different pathway from STAT1. Alternatively, OC2 could contribute to T-bet expression at some later time during Th1 development, when the stable expression of T-bet is already driven by the IFN-gR/STAT1 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated T-bet induces IL-12Rb2 and IFN-g expression, allowing IL-12R/STAT4 signaling to optimize IFN-g expression, and thereby amplifying and establishing the effector commitment of Th1 cells. [7][8][9] In addition, T-bet induces the expression of homeobox transcription factor, Hlx, and both proteins cooperate to transactivate IFN-g and T-bet expression. 10 Thus, the central roles of T-bet in the cell-extrinsic and -intrinsic pathways involved in Th1 lineage commitment have been well established.…”
Section: Introductionmentioning
confidence: 99%
“…IL-10 is known to suppress the responsiveness to IFN-c via inducing the SOCS family [24]. IFN-c activates JAK1 and JAK2, causing the phosphorylation, dimerization and nuclear translocation of STAT1, which is important for the induction of T-bet [25]. T-bet can cause not only chromatin remodeling of the IFN-c locus and transactivation of the IFN-c gene but also induces IL-12Rb2 chain expression, allowing IL-12/STAT4 signaling to optimize IFN-c production, thereby completing the Th1 development commitment process.…”
Section: Discussionmentioning
confidence: 99%
“…17 Upon activation of T cells via the T-cell receptor, both IL-12 receptor chains are induced, which is additionally enhanced by IL-12 itself, IFN-g, tumor necrosis factor-a (TNF-a) and anti-CD28 costimulation. 18,19 Successful triggering of the receptor activates the Janus kinase-STAT (signal transducer and activator of transcription) signaling pathway, predominantly leading to STAT4 phosphorylation, which mediates subsequent cellular responses. 20,21 …”
Section: Open Questionsmentioning
confidence: 99%